2023
DOI: 10.1021/acsami.2c20787
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Lithium Dendrite Suppression by Hybrid Composite Separators: Indentation Measurements Informed by Operando X-ray Computed Tomography

Abstract: This study investigates the significance of the mechanics of hybrid particle−polymer separators in the stabilization of lithium metal interfaces by probing these properties in realistic conditions informed by X-ray microcomputed tomography (micro-CT). Elastic properties and viscoelastic behavior of inorganic microparticle-filled poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) films are characterized using a nanoindentation experiment whose displacement simulates the interfacial response seen in ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 65 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…It remains to be seen whether further improvement may be possible by designing the system to also be effective at mechanically blocking dendrite growth. It was found that for particle–polymer separators, both ion transport homogeneity and mechanical enhancements should be key design considerations to achieve better lithium metal cycling . An additional coating was synthesized that consisted of an in situ cross-linked matrix of poly­(ethylene glycol) diacrylate (PEGDA, M n = 575 g mol –1 ), scaffolding the swollen particle brushes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It remains to be seen whether further improvement may be possible by designing the system to also be effective at mechanically blocking dendrite growth. It was found that for particle–polymer separators, both ion transport homogeneity and mechanical enhancements should be key design considerations to achieve better lithium metal cycling . An additional coating was synthesized that consisted of an in situ cross-linked matrix of poly­(ethylene glycol) diacrylate (PEGDA, M n = 575 g mol –1 ), scaffolding the swollen particle brushes.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining THF in the drop cast coatings was left to evaporate with gentle heating on a hot plate for an hour. The cell design was adapted from our previous work, which enabled high-quality microcomputed tomograms of lithium metal batteries . In this case, two 17 mm diameter Celgard 3501 separators (Celgard) were sandwiched by electrodes that achieved the minimum electrode separation requirement (50 μm) for optimal micro-CT resolution of lithium metal in its various morphologies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations